Epigenetic insights into Fragile X Syndrome - Xie, Liangqun; Li, Huiying; Xiao, MengLiang; Chen, Ningjing; Zang, Xiaoxiao; Liu, Yingying; Ye, Hong; Tang, Chaogang (Frontiers in Cell and Developmental Biology, 2024)
Fragile X Syndrome (FXS) is a genetic neurodevelopmental disorder closely associated with intellectual disability and autism spectrum disorders. The core of the disease lies in the abnormal expansion of the CGG trinucleotide repeat sequence at the 5' end of the FMR1 gene. When the repetition exceeds 200 times, it causes the silencing of the FMR1 gene, leading to the absence of the encoded Fragile X mental retardation protein 1 (FMRP). Although the detailed mechanism by which the CGG repeat expansion triggers gene silencing is yet to be fully elucidated, it is known that this process does not alter the promoter region or the coding sequence of the FMR1 gene. This discovery provides a scientific basis for the potential reversal of FMR1 gene silencing through interventional approaches, thereby improving the symptoms of FXS. Epigenetics, a mechanism of genetic regulation that does not depend on changes in the DNA sequence, has become a new focus in FXS research by modulating gene expression in a reversible manner. The latest progress in molecular genetics has revealed that epigenetics plays a key role in the pathogenesis and pathophysiological processes of FXS. This article compiles the existing research findings on the role of epigenetics in Fragile X Syndrome (FXS) with the aim of deepening the understanding of the pathogenesis of FXS to identify potential targets for new therapeutic strategies.